2011
DOI: 10.1186/1743-7075-8-81
|View full text |Cite
|
Sign up to set email alerts
|

A higher response of plasma neuropeptide Y, growth hormone, leptin levels and extracellular glycerol levels in subcutaneous abdominal adipose tissue to Acipimox during exercise in patients with bulimia nervosa: single-blind, randomized, microdialysis study

Abstract: BackgroundNeuropeptide Y (NPY) is an important central orexigenic hormone predominantly produced by the hypothalamus, and recently found to be secreted in adipose tissue (AT). Acipimox (Aci) inhibits lipolysis in AT and reduces plasma glycerol and free fatty acid (FFA) levels. Exercise and Aci are enhancers of growth hormone (GH) and NPY secretion and exercise may alter leptin levels. We expect to find abnormal neuropeptidergic response in plasma and AT in patients with bulimia nervosa (BN). We hypothesize tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…In our previous studies, we observed in vivo increased SNS activity in subcutaneous abdominal AT in AN and BN patients [6, 33–36]. The cause and pathogenesis of AN and BN, however, remain unknown.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our previous studies, we observed in vivo increased SNS activity in subcutaneous abdominal AT in AN and BN patients [6, 33–36]. The cause and pathogenesis of AN and BN, however, remain unknown.…”
Section: Introductionmentioning
confidence: 92%
“…It has been reported that NPY can attenuate specific behavior when the organism is stressed, and antistress effects of NPY are relevant to psychiatric conditions such as AN and BN [6, 155, 156] and that NPY has an anxiolytic and antidepressive behavior profile [157]. Interestingly, it is possible that NPY contributes to both binge eating and subsequent purging in BN because NPY itself has been demonstrated to induce an emetic response [158].…”
Section: An Overview Of Hunger-satiety Signals and Autoantibodies mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoleptinaemia is actually accompanied by a decrease in basal energy expenditure in women with amenorrhea. Indeed, in anorexia nervosa (AN) and bulimia nervosa (BN) patients, plasma leptin levels were found to be lower than in normal weight controls (Nedvídková et al, 2000;Dostálová et al, 2007;Smitka et al, 2011Smitka et al, , 2013a. However, realimentation leads to an increase in plasma leptin levels in AN and BN patients.…”
Section: Leptinmentioning
confidence: 99%
“…On the other hand, neuropeptide Y, produced by hypothalamus and adipose tissue, together with ghrelin, produced by stomach and involved in short term regulation of feeding and long term regulation of energy metabolism, are both orexigenic hormones. [4][5][6][7][8][9] In addition to hypothalamic satiety center, receptors for leptin, ghrelin, resistin and neuropeptide Y have been identified in limbic areas of the brain that regulate emotion. 10,11 Among the most prevalent mental illnesses, depression is increasing in the western world and these peptides were reported to play a role in emergence of emotional disturbances like depression.…”
Section: Introductionmentioning
confidence: 99%